2013
DOI: 10.1038/ejcn.2013.64
|View full text |Cite
|
Sign up to set email alerts
|

Preference for salt contributes to sympathovagal imbalance in the genesis of prehypertension

Abstract: Salt preference is associated with sympathovagal imbalance caused by sympathetic overactivity and vagal withdrawal. Sympathovagal imbalance is more intense in salt-preferring prehypertensives compared with salt-preferring normotensives. Sympathovagal imbalance in salt-preferring subjects is independent of BMI. Thus, salt-preferring subjects should be encouraged to restrict salt intake to maintain their sympathovagal balance and BP homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 41 publications
1
11
1
Order By: Relevance
“…The difference of salt liking score between obese and normal-weight subjects was moderate and of the same extent in men and women. This result does not concur with previous sensory studies, 8,11,17,18 except with the observations of Hashimoto et al 19 in women. It is likely that the present result would not have been significant in a smaller population sample, such as used in most studies.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…The difference of salt liking score between obese and normal-weight subjects was moderate and of the same extent in men and women. This result does not concur with previous sensory studies, 8,11,17,18 except with the observations of Hashimoto et al 19 in women. It is likely that the present result would not have been significant in a smaller population sample, such as used in most studies.…”
Section: Discussioncontrasting
confidence: 72%
“…16 Regarding salt liking, some studies have observed no difference across BMI categories 11,14 or no difference of BMI between salt-preference groups. 17 Others have shown that overweight or obese subjects liked a salty solution less than normalweight subjects. 8,18 In contrast, overweight women were shown to have a stronger salt liking than normal-weight and obese women.…”
Section: Introductionmentioning
confidence: 99%
“…Namely, in established cases of hypertension, dietary sodium restriction seems to further alter sympathovagal balance, ie, to impair reflex sympathetic control, and to concomitantly further increase the number of sympathetic bursts to the skeletal muscle circulation. [106][107][108] The effect is marked when the sodium restraint is marked as well but present even with moderately low-sodium intake (80 mmol NaCl/d), 107 suggesting that a low-sodium diet, as usually implemented in daily life, enhances the hypertension-related alterations of autonomic cardiovascular control.…”
Section: Autonomic Alterations During Pharmacological and Nonpharmacomentioning
confidence: 99%
“…In normotensives, to maintain BP, the heart and peripheral vessels seem to accommodate to the changes in plasma volume that follow changes in Na + consumption. [8] When Na + intake is high, there will be increase in extracellular fluid volume, increase in blood volume, increase in wall stretch in the heart and blood vessels, increase in the discharge rate of baroreceptors and the resultant decrease in cardiac activity and vascular tone. There will be the reverse mechanism when the Na + intake is low.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Pal and colleagues reported that salt predilection is associated with sympathovagal imbalance in the form of sympathetic overactivity and vagal withdrawal in young Indian normotensives. [8] However, Luft and associates discovered that sympathetic nervous system activity appears to decrease with salt loading in normal subjects. [9] McNeely and his co-workers found the increased vagal tone in normotensive persons on high salt intake.…”
Section: Introductionmentioning
confidence: 99%